Resilience, Social Support, and Parenting Self-Efficacy: Insights from Young Mothers Married as Children - Hermita, Matrissya; Rohani, Alia; Suhatril, Ruddy J (Islamic Guidance and Counseling Journal, 2025)
Child marriage represents a significant social concern with persistent consequences for the well-being of women and children.  It adversely influences young mothers’ quality of life and their parenting practices, particularly their confidence and readiness to fulfill parental responsibilities effectively. However, limited research has systematically examined how resilience and distinct types of social support influence parenting self-efficacy (PSE) among this vulnerable population. This study aims to examine the distinct and combined contributions of resilience and social support to PSE, systematically comparing the effects of each support type on PSE among young mothers who have experienced child marriage. Furthermore, it explores how demographic factors, including marital status and reasons for marriage, are associated with variations in PSE. A cross-sectional design with purposive sampling was employed, with a sample of 110 young mothers who experience child marriage. Structured questionnaires were administered, including demographic items, the Early Intervention Parenting Self-Efficacy Scale, the Connor-Davidson Resilience Scale, and the Social Provisions Scale. Multiple regression analysis, including Analysis of Variance (ANOVA) and Multidimensional Scaling (MDS), was conducted to assess the factors influencing PSE. The results indicate that resilience and social support significantly predict PSE (R² = .630, p < .01), with social support emerging as the strongest predictor. These findings suggest that enhancing resilience and social support for young mothers can substantially improve their parenting efficacy.